Foreign Body of the Right Main Bronchus with Tracheal Perforation (Case Report) - V. N. Stalmahovich (Scientific Сentre for Family Health and Human Reproduction Problems, 2019)
The article describes a rare case of a foreign body removal from the tracheobronchial tree of a child. In the acute period of aspiration, the girl developed severe hypoxia, a terminal condition caused by the standing of a foreign body in the infraglottic space, a spasm of the vocal cords and obstruction of the lumen of the respiratory tract. In emergency tracheal intubation in a medical institution at the place of residence, the foreign body was moved more distally, which allowed to restore lung ventilation, stabilize the child’s condition and transport her to a specialized medical institution where X-ray and endoscopic examination were performed. It was found that the one-year-old patient had a screw cap tightly wedged into the lumen of the right main bronchus, and the screw’s opposite sharp end punched the left wall of the trachea above its carina. There was a potentially high risk of perforation of the main vessels of the mediastinum with massive bleeding and an unfavorable outcome. Endoscopic removal of a foreign body was technically impossible due to the peculiarity of its transverse arrangement and perforation of the wall, which served as an indication for emergency thoracotomy. A longitudinal sternotomy was performed, providing good access to the distal trachea, the main bronchi and the great vessels. Then we performed transverse bronchotomy in the initial part of the right main bronchus on half of its circumference, removed the foreign body, sutured the wall of the bronchus. The length of the extracted self-drilling screw was 35 millimeters. Postoperative early and late periods went without complications. At follow-up, mucosal surface of the right main bronchus was pink, the vascular pattern was visible, the bronchus was freely passable, not deformed.